1997
DOI: 10.1029/97jd01335
|View full text |Cite
|
Sign up to set email alerts
|

Variation of snow cover ablation in the boreal forest: A sensitivity study on the effects of conifer canopy

Abstract: Abstract. The duration and meteorological history of winter and thaw periods in the boreal forest affect carbon exchange during the growing season. Characteristics of conifer canopies exert important control on the energy exchange at the forest floor, which in turn controls snow cover processes such as melting. This analysis investigated the role of the conifer tree characteristics, including height and canopy density. Canopy and snow models estimated radiation incoming to the snow surface, the net energy budg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 24 publications
4
63
0
Order By: Relevance
“…By comparing adjacent forest and field sites, Zhang et al (2005) and Reba (2012) showed that snowpack sublimation is smaller in forests, mainly because of lower wind and net radiation, the latter of which is very sensitive to canopy characteristics (Davis et al, 1997). Furthermore, as Dery and Yau (2002) showed, the relative air humidity with respect to ice is lower in western Siberia than the east, so sublimation is likely to be higher in the western sector as it also dominated by field cover.…”
Section: E Kantzas Et Al: Evaluation Of the Snow Regimementioning
confidence: 99%
“…By comparing adjacent forest and field sites, Zhang et al (2005) and Reba (2012) showed that snowpack sublimation is smaller in forests, mainly because of lower wind and net radiation, the latter of which is very sensitive to canopy characteristics (Davis et al, 1997). Furthermore, as Dery and Yau (2002) showed, the relative air humidity with respect to ice is lower in western Siberia than the east, so sublimation is likely to be higher in the western sector as it also dominated by field cover.…”
Section: E Kantzas Et Al: Evaluation Of the Snow Regimementioning
confidence: 99%
“…Studies of the sensitivity of snowmelt to canopy coverage have generally been based on modeling results (Yamazaki and Kondo 1992;Davis et al 1997), as the difficulty of observing different snowmelt rates under various canopy covers is large. Suzuki and Ohta (2003) simulated snowmelt rates under larch forests of different densities.…”
Section: Introductionmentioning
confidence: 99%
“…While tundra and lake-rich landscapes show a smaller variability in spring, forest landscapes show a smaller variability in autumn. The high variability of forest landscapes in spring could be attributed to snow melt, which is a heterogeneous process in forest-dominated landscapes [63]. Park et al [35] found different relationships for the spring transition date and the timing of snow melt for tundra and forest environments.…”
Section: Importance Of Landscape Types On the Issue Of Scalementioning
confidence: 99%